A q triple product integral

Calculus Level 5

0 1 k = 1 ( 1 q 6 k ) ( 1 + q 6 k 1 ) ( 1 + q 6 k 5 ) d q = π a × e π a 5 2 b c e π a 5 2 b + e π a 3 2 b + c \int _{ 0 }^{ 1}{ \prod _{ k=1 }^{ \infty }{ \left( 1-{ q }^{ 6k } \right) \left( 1+{ q }^{ 6k-1 } \right) \left( 1+{ q }^{ 6k-5 } \right) } dq=\frac { \pi }{ \sqrt { a } } \times \frac { { e }^{ \frac { \pi { a }^{ \frac { 5 }{ 2 } } }{ b } }- c }{ { e }^{ \frac { \pi { a }^{ \frac { 5 }{ 2 } } }{ b } }+{ e }^{ \frac { \pi { a }^{ \frac { 3 }{ 2 } } }{ b } }+ c } }

In the above given expression find the value of a a , b b , c c (which are positive and co-prime to each other) and submit the answer as the sum of a + b + c a+b+c


The answer is 6.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Wesley Low
Aug 11, 2020

Lemma: n = 1 ( n a ) 2 + b 2 = π b tanh π b sec 2 π a tan 2 π a + tanh 2 π b \sum_{n=-\infty}^{\infty} {\dfrac{1}{\left(n-a\right)^2+b^2}}=\dfrac{\pi}{b}\dfrac{\tanh \pi b \sec^2 \pi a}{\tan^2 \pi a + \tanh^2 \pi b}

Proof: Consider the function f ( z ) = π ( ( z a ) 2 + b 2 ) tan π z f\left(z\right)=\dfrac{\pi}{\left(\left(z-a\right)^2+b^2\right)\tan{\pi z}} This function has simple poles at z = a ± b i z=a\pm bi and n , n Z n, \forall n\in\Z . The residues at these poles are Res ( f ( z ) , a ± b i ) = ± π 2 b i tan ( π ( a ± b i ) ) \text{Res}\left(f\left(z\right), a\pm bi\right)=\dfrac{\pm \pi}{2bi\tan{\left(\pi \left(a \pm bi\right)\right)}} Res ( f ( z ) , n ) = 1 ( n a ) 2 + b 2 \text{Res}\left(f\left(z\right), n\right)=\dfrac{1}{\left(n-a\right)^2+b^2} Consider a square contour defined by the vertices ( N + 1 2 ) ( ± 1 ± i ) \left(N+\dfrac{1}{2}\right)\left(\pm1\pm i\right) , where N Z + , N > max ( a , b ) N\in\Z^+, N>\max\left(a,b\right) . We denote this contour as Γ N \Gamma_N .

By Cauchy's Residue Theorem, we have Γ N f ( z ) = 2 π i ( Res ( f ( z ) , a ± b i ) + n = N N Res ( f ( z ) , n ) ) \oint_{\Gamma_N}f\left(z\right)=2\pi i\left(\text{Res}\left(f\left(z\right), a\pm bi\right)+\sum_{n=-N}^{N}\text{Res}\left(f\left(z\right), n\right)\right) Γ N f ( z ) = 2 π i ( π 2 b i tan ( π ( a + b i ) ) π 2 b i tan ( π ( a b i ) ) + n = N N 1 ( n a ) 2 + b 2 ) \oint_{\Gamma_N} f\left(z\right) =2\pi i\left(\dfrac{ \pi}{2bi\tan{\left(\pi \left(a +bi\right)\right)}}-\dfrac{\pi}{2bi\tan{\left(\pi \left(a -bi\right)\right)}}+\sum_{n=-N}^{N} {\dfrac{1}{\left(n-a\right)^2+b^2}}\right) Γ N f ( z ) = 2 π i ( π b tanh π b sec 2 π a tan 2 π a + tanh 2 π b + n = N N 1 ( n a ) 2 + b 2 ) \oint_{\Gamma_N} f\left(z\right) =2\pi i\left(\dfrac{-\pi}{b}\dfrac{\tanh \pi b \sec^2 \pi a}{\tan^2 \pi a + \tanh^2 \pi b}+\sum_{n=-N}^{N} {\dfrac{1}{\left(n-a\right)^2+b^2}}\right) Now we prove that the limit of the LHS as N N\to \infty is 0. We can show that for all values of z z along Γ N \Gamma_N , 1 tan ( z ) \left|\dfrac{1}{\tan\left(z\right)}\right| is maximised at z = ( N + 1 2 ) i z=\left(N+\dfrac{1}{2}\right)i , thus 1 tan ( z ) 1 tan ( ( N + 1 2 ) i ) = coth ( N + 1 2 ) \left|\dfrac{1}{\tan\left(z\right)}\right|\leq \left|\dfrac{1}{\tan\left(\left(N+\dfrac{1}{2}\right)i\right)}\right|=\coth{\left(N+\dfrac{1}{2}\right)} Hence by the estimation lemma, Γ N f ( z ) Length ( Γ N ) sup z Γ N f ( z ) 4 ( 2 N + 1 ) sup z Γ N 1 tan ( z ) π ( z a ) 2 + b 2 4 ( 2 N + 1 ) coth ( N + 1 2 ) O ( 1 N 2 ) \left|\oint_{\Gamma_N} f\left(z\right) \right|\leq \text{Length}\left(\Gamma_N\right)\text{sup}_{z \in \Gamma_N} \left|f\left(z\right)\right|\leq 4\left(2N+1\right)\text{sup}_{z \in \Gamma_N} \left|\dfrac{1}{\tan\left(z\right)}\right|\left|\dfrac{\pi}{\left(z-a\right)^2+b^2}\right|\leq4\left(2N+1\right)\coth{\left(N+\dfrac{1}{2}\right)}\mathcal{O}\left(\dfrac{1}{N^2}\right) Taking the limit as N N\to\infty , we get Γ f ( z ) = 0 \left|\oint_{\Gamma_\infty} f\left(z\right) \right|=0 0 = 2 π i ( π b tanh π b sec 2 π a tan 2 π a + tanh 2 π b + n = 1 ( n a ) 2 + b 2 ) 0=2\pi i\left(\dfrac{-\pi}{b}\dfrac{\tanh \pi b \sec^2 \pi a}{\tan^2 \pi a + \tanh^2 \pi b}+\sum_{n=-\infty}^{\infty} {\dfrac{1}{\left(n-a\right)^2+b^2}}\right) n = 1 ( n a ) 2 + b 2 = π b tanh π b sec 2 π a tan 2 π a + tanh 2 π b \sum_{n=-\infty}^{\infty} {\dfrac{1}{\left(n-a\right)^2+b^2}}=\dfrac{\pi}{b}\dfrac{\tanh \pi b \sec^2 \pi a}{\tan^2 \pi a + \tanh^2 \pi b} QED


Using Jacobi's triple product, we can simplify the integral as such 0 1 k = 1 ( 1 q 6 k ) ( 1 + q 6 k 1 ) ( 1 + q 6 k 5 ) d q = 0 1 n = q 3 n 2 + 2 n d q \int_0^1 \prod_{k=1}^{\infty} \left(1-q^{6k}\right)\left(1+q^{6k-1}\right)\left(1+q^{6k-5}\right)dq =\int_0^1 \sum_{n=-\infty}^{\infty}q^{3n^2+2n}dq = n = 1 3 n 2 + 2 n + 1 =\sum_{n=-\infty}^{\infty} \dfrac{1}{3n^2+2n+1} = 1 3 n = 1 ( n + 1 3 ) 2 + ( 2 3 ) 2 =\dfrac{1}{3}\sum_{n=-\infty}^{\infty} \dfrac{1}{\left(n+\dfrac{1}{3}\right)^2+\left(\dfrac{\sqrt{2}}{3}\right)^2} By our lemma, this equals π 2 tanh ( 2 π 3 ) sec 2 ( π 3 ) tan 2 ( π 3 ) + tanh 2 ( 2 π 3 ) \dfrac{\pi}{\sqrt{2}}\dfrac{\tanh \left(\dfrac{\sqrt{2}\pi}{3}\right) \sec^2 \left(-\dfrac{\pi}{3}\right)}{\tan^2 \left(\dfrac{-\pi}{3}\right) + \tanh^2 \left( \dfrac{\sqrt{2}\pi}{3}\right)} After simplifying, we get π 2 e 4 2 3 π 1 e 4 2 3 π + e 2 2 3 π + 1 = π 2 e 2 5 2 3 π 1 e 2 5 2 3 π + e 2 3 2 3 π + 1 \dfrac{\pi}{\sqrt2}\dfrac{e^{\frac{4\sqrt2}{3}\pi}-1}{e^{\frac{4\sqrt2}{3}\pi}+e^{\frac{2\sqrt2}{3}\pi}+1} =\dfrac{\pi}{\sqrt2}\dfrac{e^{\frac{2^\frac{5}{2}}{3}\pi}-1}{e^{\frac{2^\frac{5}{2}}{3}\pi}+e^{\frac{2^\frac{3}{2}}{3}\pi}+1} Hence a + b + c = 2 + 3 + 1 = 6 a+b+c=2+3+1=\boxed{6} .

beautiful solution brother :) keep it up

Syed Shahabudeen - 10 months ago
Syed Shahabudeen
Aug 11, 2020

0 1 k = 0 ( 1 q 6 k + 6 ) ( 1 + q 6 k + 5 ) ( 1 + q 6 k + 1 ) d q = 0 1 ( q 6 ; q 6 ) ( q 5 ; q 6 ) ( q ; q 6 ) d q Where ( a ; q ) = k = 0 ( 1 a q k ) = 0 1 n = q 3 n 2 + 2 n d q = n = 1 3 n 2 + 2 n + 1 = π 2 sinh ( 2 π 2 3 ) ( cosh ( 2 π 2 3 ) cos ( 2 π 3 ) ) = π 2 e π 2 5 2 3 1 e π 2 5 2 3 + e π 2 3 2 3 + 1 therefore a + b + c = 6 \begin{aligned} \int_{0}^{1} {\prod _{ k=0 }^{ \infty }{ \left( 1-{ q }^{ 6k+6 } \right) \left( 1+{ q }^{ 6k+5 } \right) \left( 1+{ q }^{ 6k+1 } \right) } dq}&=\int_{0}^{1}{{ \left( { q }^{ 6 };{ q }^{ 6 } \right) }_{ \infty }{ \left( { -q }^{ 5 };{ q }^{ 6 } \right) }_{ \infty }{ \left( { -q };{ q }^{ 6 } \right) }_{ \infty }dq}&&&&&&& \textrm{Where} \quad (a;q)_{\infty}&=\prod_{k=0}^{\infty}{(1-aq^{k})}\\&=\int_{0}^{1}{\sum _{ n=-\infty }^{ \infty }{ { q }^{ 3{ n }^{ 2 }+2n } }dq }\\&=\sum _{ n=-\infty }^{ \infty }{\frac{1}{3n^{2}+2n+1}} \\&=\frac { \pi }{ \sqrt { 2 } } \frac { \sinh { \left( \frac { 2\pi \sqrt { 2 } }{ 3 } \right) } }{ \left( \cosh { \left( \frac { 2\pi \sqrt { 2 } }{ 3 } \right) -\cos \left( \frac { 2\pi }{ 3 } \right) } \right) }\\&= { \frac { \pi }{ \sqrt { 2 } } \frac { { e }^{ \frac { \pi { 2 }^{ \frac { 5 }{ 2 } } }{ 3 } }-1 }{ { e }^{ \frac { \pi { 2 }^{ \frac { 5 }{ 2 } } }{ 3 } }+{ e }^{ \frac { \pi { 2 }^{ \frac { 3 }{ 2 } } }{ 3 } }+1 } }\\\textrm{therefore}\quad\boxed{a+b+c=6} \end{aligned}

For the series of the form n = 1 a n 2 + b n + 1 \displaystyle\sum _{ n=-\infty }^{ \infty }{\frac{1}{an^{2}+bn+1}} refer this paper .

proof for n = q 3 n 2 + 2 n d q = ( q 6 ; q 6 ) ( q 5 ; q 6 ) ( q ; q 6 ) \sum _{ n=-\infty }^{ \infty }{{ { q }^{ 3{ n }^{ 2 }+2n } }dq }={ { \left( { q }^{ 6 };{ q }^{ 6 } \right) }_{ \infty }{ \left( { -q }^{ 5 };{ q }^{ 6 } \right) }_{ \infty }{ \left( { -q };{ q }^{ 6 } \right) }} can be found out by substituting a = q 5 a=q^{5} and b = q b=q in Ramanujan Theta functions which states that f ( a , b ) = n = a n ( n + 1 ) 2 b n ( n 1 ) 2 = ( a ; a b ) ( b ; a b ) ( a b ; a b ) f\left( a,b \right) =\sum _{ n=-\infty }^{ \infty }{ { a }^{ \frac { n(n+1) }{ 2 } }{ b }^{ \frac { n(n-1) }{ 2 } } } ={ \left( -a;ab \right) }_{ \infty }{ \left( -b;ab \right) }_{ \infty }{ \left( ab;ab \right) }_{ \infty }

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...